IMPLEMENTASI PROGRAM DANA BANTUAN OPERASIONAL SEKOLAH (BOS) TINGKAT PENDIDIKAN DASAR PADA MASA PANDEMI COVID-19 DI KABUPATEN BANDUNG PROVINSI JAWA BARAT - Udaya Madjid; Agung Nurrahman; Nurul Wahyuni (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2021)
ABSTRACT. The School Operational Assistance Fund is the government's effort in increasing the achievement of the Compulsory Education Program, this cannot be separated from the situation during the current pandemic. The Ministry of Education and Culture of the Republic of Indonesia issued a circular regarding the use of School Operational Assistance funds during the pandemic, in this circular there were several changes to the policy on the allocation of funds and the emphasis on allocation related to preventing the transmission of Covid-19. The purpose of the study was to obtain an overview and describe the implementation of the distribution of School Operational Assistance funds in Bandung Regency during the Covid-19 pandemic. The method used is descriptive qualitative research method with data collection techniques in the form of observation, interviews, and documentation, while in analyzing the data the author uses three activity lines, namely data reduction, data presentation, and drawing conclusions. The findings of this study are that there are still schools that do not participate in socialization activities so that the implications for socialization are less than optimal because the socialization is less targeted. The conclusion that the authors take is that the implementation of BOS distribution in the Regency has not been maximized, this is because there are still indicators that have not been fulfilled in its implementation, especially those in the dimensions of communication and resources. Therefore, the authors suggest to local governments to improve the ability of schools in managing BOS funds through improving facilities and infrastructure, socializing, training, and hiring employees who have basic financial management.Keywords: Implementation, School Operational Assistance Fund, Basic Education